1990
DOI: 10.1002/eji.1830200416
|View full text |Cite
|
Sign up to set email alerts
|

New B cell epitopes in the Plasmodium falciparum malaria circumsporozoite protein

Abstract: Most antibodies directed against the Plasmodium falciparum circumsporozoite (CS) protein react with its central domain, which contains about 40 repeats of the tetrapeptide Asn-Ala-Asn-Pro (NANP). To search for new epitopes in the non-repetitive part of the CS protein, we expressed the non-repetitive regions of the protein in E. coli as fusion proteins with mouse dihydrofolate reductase linked to six adjacent histidine residues. These fusion proteins were obtained at greater than 70% purity by a single Ni-chela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…This sequence was identified as a B-cell epitope in two independent studies in Africa (9, 47) but was found to be nonresponsive in C57BL/6 mice when delivered in complete Freund's adjuvant (9). The second epitope (S-11b) was first identified based on its reactivity with an anti-CSP MAb generated in BALB/c mice (53) and recognition by sera from individuals living in Papua New Guinea and Brazil (47). Our studies suggest that while these B-cell epitopes are individually recognized by some individuals living in areas where malaria is endemic, when presented as a combination epitope in a MAP vaccine, they are not effective B-cell epitopes in mice.…”
Section: Discussionmentioning
confidence: 99%
“…This sequence was identified as a B-cell epitope in two independent studies in Africa (9, 47) but was found to be nonresponsive in C57BL/6 mice when delivered in complete Freund's adjuvant (9). The second epitope (S-11b) was first identified based on its reactivity with an anti-CSP MAb generated in BALB/c mice (53) and recognition by sera from individuals living in Papua New Guinea and Brazil (47). Our studies suggest that while these B-cell epitopes are individually recognized by some individuals living in areas where malaria is endemic, when presented as a combination epitope in a MAP vaccine, they are not effective B-cell epitopes in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our results confirmed the presence of B cell epitopes in the non-repetitive regions of the Pf CSP. [10][11][12][13][14][15][16][17]27 However, in all three ethnic groups, the seroprevalence for both the N-and C-terminal regions of Pf CSP was lower than that recorded for the central repetitive domain.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] The involvement of CSP in the invasion of sporozoites into hepatocytes has been shown by Cerami and others. 9 The flanking non-repeat regions of CSP contain several epitopes recognized not only by antibodies, [10][11][12][13][14][15][16][17] but also by CD4 ϩ T helper cells [18][19][20] and CD8 ϩ cytotoxic T lymphocytes. [21][22][23][24] Vaccine candidates based on the immunodominant, repetitive domain of the P. falciparum CSP (Pf CSP) gave unsatisfactory results in terms of protection of human volunteers.…”
mentioning
confidence: 99%
“…Antibodies and Inhibitors-We used previously characterized anti-P. falciparum AMA-1 (PfAMA-1) domain III monoclonal antibody (mAb) DV5 (8), anti-PfAMA-1 prodomain mAb 5G8 (9), anti-PfAMA-1 domain I mAb 1F9 (9), anti-3D7 strain PfAMA-1 polyclonal rabbit IgG (10), anti-FVO strain PfAMA-1 polyclonal rabbit IgG (11), anti-PfTRAP mAb SSP2.2 (12), and anti-PfCSP mAb E9 (13). For liver schizont counting, we used anti-Plasmodium HSP-70 sera obtained from mice immunized with i72 recombinant protein (gift from D. Mattei, Institut Pasteur, Paris, France).…”
Section: Methodsmentioning
confidence: 99%